ProjecToR: Agile Reconfigurable Data Center Interconnect - Ghobadi, Manya; Mahajan, Ratul; Phanishayee, Amar; Devanur, Nikhil; Kulkarni, Janardhan (Jana); Ranade, Gireeja; Blanche, Pierre-Alexandre; Rastegarfar, Houman; Glick, Madeleine; Kilper, Daniel (ACM SIGCOMM 2016, 2016)
We explore a novel, free-space optics based approach for building data center interconnects. It uses a digital micromirror device (DMD) and mirror assembly combination as a transmitter and a photodetector on top of the rack as a receiver. Our approach enables all pairs of racks to establish direct links, and we can reconfigure such links (i.e., connect different rack pairs) within 12 us. To carry traffic from a source to a destination rack, transmitters and receivers in our interconnect can be dynamically linked in millions of ways. We develop topology construction and routing methods to exploit this flexibility, including a flow scheduling algorithm that is a constant factor approximation to the offline optimal solution. Experiments with a small prototype point to the feasibility of our approach. Simulations using realistic data center workloads show that, compared to the conventional folded-Clos interconnect, our approach can improve mean flow completion time by 30-95% and reduce cost by 25-40%. More details here.